Assessment of a multimarker strategy for prediction of mortality in older heart failure patients: a cohort study. Issue 3 (9th March 2013) - Bjurman, Christian; Jensen, Juliana; Petzold, Max; Hammarsten, Ola; Fu, Michael L X
Abstract : Objective: Primarily to develop a multimarker score for prediction of 3-year mortality in older patients with decompensated heart failure (HF). Design: Prospective cohort study. Setting: Secondary care. Single centre. Patients and biomarkers: 131 patients, aged ≥65 years, with decompensated HF were included. Assessment of biomarkers was performed at discharge. Primary outcome measure: 3-year mortality. Results: Mean age was 73±11 years; mean left ventricular ejection fraction, 43±14%; 53% were male. The 3-year mortality was 53.4%. The following N-terminal brain natriuretic peptide (NTproBNP) levels could optimally stratify mortality: <2000 ng/l (n=39), 30.8% mortality; 2000–8000 ng/l (n=58), 51.7% mortality; and >8000 ng/l (n=34), 82.4% mortality. However, in the 2000–8000 ng/l range, NTproBNP levels had low-prognostic capacity, based on the area under the receiver operating characteristic curve (AUC=0.53; 95% CI 0.40 to 0.67). In this group, multivariate analysis identified age, cystatin C (CysC), and troponin T (TnT) levels as independent risk factors. A risk score based on these three risk factors separated a high-risk and low-risk groups within the NTproBNP range of 2000–8000 ng/l. The score exhibited a significantly higher AUC (0.75; 95% CI 0.62 to 0.86) than NTproBNP alone (p=0.03) in this NTproBNP group and had similar prognostic capacity as NTproBNP in patients below or above this NTproBNP range (p=0.57). Net reclassification improvement and integrated discriminatory improvement in the group with NTproBNP levels between 2000 and 8000 ng/l was 54% and 23%, respectively, and in the whole cohort 22% and 11%, respectively. Conclusions: Our results suggested that, to assess risk in HF, older patients required significantly higher levels of NTproBNP than younger patients. Furthermore, a risk score that included TnT and CysC at discharge, and age could improve risk stratification for mortality in older patients with HF in particular when NTproBNP was moderately elevated.